2018
DOI: 10.1080/07420528.2018.1474890
|View full text |Cite
|
Sign up to set email alerts
|

Chronotherapy of maxacalcitol on skin inflammation induced by topical 12-O-tetradecanoylphorbol-13-acetate in mice

Abstract: In general, chronotherapy is desirable for a more effective and/or safe dosage regimen. In this study, a daily rhythm of skin vitamin D receptor (VDR) and chronotherapeutic profiles of maxacalcitol, a vitamin D analogue, were evaluated using mice with skin inflammation induced by topical 12-O-tetradecanoylphorbol-13-acetate (TPA). This study showed that skin nuclear VDR expression in TPA-treated mice has a daily rhythm with the peak at the middle of active period. The effects of maxacalcitol were greater after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Moreover, all rhythms in infection are abolished in clock-deficient macrophages and mice lacking the circadian clock in immune cells [47]. Additionally, the diurnal pattern of T-cell recruitment and function parallels nocturnal itching and exaggeration in atopic dermatitis (AD) [48].…”
Section: The Skin Immune System Is Circadian Clockregulatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, all rhythms in infection are abolished in clock-deficient macrophages and mice lacking the circadian clock in immune cells [47]. Additionally, the diurnal pattern of T-cell recruitment and function parallels nocturnal itching and exaggeration in atopic dermatitis (AD) [48].…”
Section: The Skin Immune System Is Circadian Clockregulatedmentioning
confidence: 99%
“…Hence, more clinical studies should be conducted to assess how time of application impacts treatment efficacy and side effects. Experiments done in mice show that maxacalcitol, a vitamin D3 analogue for psoriasis symptom relief, is more effective when applied during the early to middle active phase of mice than during the early to middle resting phase [48]. For AD, application of topical treatment in the evening is proposed to improve symptoms [156].…”
Section: Chronotherapymentioning
confidence: 99%
“…59,60 Studies using a murine model of psoriasis-like inflammation demonstrated that the expression of the vitamin D receptor (VDR) exhibits diurnal variation with VDR levels peaking in the middle of the active period (night-time for nocturnal animals such as mice). 61 Using this model, the authors demonstrated that the efficacy of topical vitamin D analogues, one of the first-line treatments for psoriasis, was enhanced when administered during early to middle active period compared with dosing during early to middle inactive period. 61 A recent study demonstrated greater efficacy of topical corticosteroids when applied to plaques of psoriasis in the evening.…”
Section: Chronother Apymentioning
confidence: 99%
“… 61 Using this model, the authors demonstrated that the efficacy of topical vitamin D analogues, one of the first‐line treatments for psoriasis, was enhanced when administered during early to middle active period compared with dosing during early to middle inactive period. 61 A recent study demonstrated greater efficacy of topical corticosteroids when applied to plaques of psoriasis in the evening. 62 Similar observations come from several small clinical studies, in which administration of corticosteroids for the treatment of asthma 63 and rheumatoid arthritis 64 in the afternoon or evening is more efficacious than in the morning.…”
Section: Chronotherapymentioning
confidence: 99%
“…Over the years, the circadian regulation of drug metabolism and processing has been employed in the treatment of a range of disease states, including diabetes, hypertension, peptic ulcers, and allergic rhinitis [ 58 ]. There is also interest in using chronotherapeutic approaches for skin disease, including psoriasis [ 110 ] and atopic dermatitis [ 111 ]. Although time-dictated drug administration had been demonstrated many decades ago, its application in cancer treatment was limited due to insufficient mechanistic data supporting experimental results and inconsistency among clinical trials.…”
Section: The Circadian Clock and Disease Treatmentmentioning
confidence: 99%